Sharenting and Child Privacy: The GDPR as a Benchmark for Indonesian and Thai Legal Frameworks - Ampuan Situmeang; Abdurrakhman Alhakim; Ruetaitip Chansrakaeo; Winda Fitri; Winsherly Tan (Universitas Negeri Semarang, 2026)
The increasing trend of sharenting, which refers to parents sharing respective children's data on social media, has been observed to pose significant legal challenges regarding child privacy rights in Indonesia and Thailand. Therefore, this research aims to investigate the adequacy of Personal Data Protection frameworks in both Indonesia and Thailand, particularly in the face of associated risks of sharenting to data privacy amid rising digital exposures. The objective of the investigation is to evaluate the adequacy of Indonesia’s Personal Data Protection Law and Thailand’s Personal Data Protection Act (PDPA) in safeguarding privacy of children within the digital sphere, using the European Union’s GDPR as a benchmark for best practices. Adopting a normative legal research method, this exploration systematically analyses primary and secondary legal sources to identify normative gaps and implementation challenges. The obtained results showed that both Indonesia and Thailand lack comprehensive legal safeguards that were explicitly designed to protect children’s digital privacy, with limitations in areas such as age thresholds for consent, the right to be forgotten, restrictions on profiling, and clear enforcement mechanisms. These normative deficiencies might position the relevant frameworks in an inadequate position to protect privacy rights of children in the increasingly digitalized world, where digital information can have a wide range of impacts on the present and the future development of the demographic. Compared to the GDPR, which provides explicit, robust child-specific protections, frameworks used by both observed countries remain insufficient in addressing the risks of sharenting. Accordingly, this research concludes that in order to effectively protect children’s privacy rights in the digital age, Indonesia and Thailand must reform respective legal frameworks to correspond with international privacy standards, to ensure that children's rights and digital autonomy are safeguarded amid growing parental social media disclosures and digital risks.